Penerapan Model Pembelajaran Round Club Untuk Meningkatkan Keaktifan Dan Hasil Belajar Siswa - Adiyatma; Nur Rohman; Hendra SH (Pendidikan Guru Madrasah Ibtidaiyah, Universitas Nahdlatul Ulama Purwokerto, 2025)
This study aims to determine the application of the Round Club learning model in increasing student activities in Grade IV of MIN 3 West Aceh. The approach used in this study is qualitative, specifically Classroom Action Research (CAR). The subjects in this study were 18 students in grade IV of MIN 3 West Aceh. The data collection techniques used are observation and testing techniques. The results showed that in pre-action, only 4 students, or 22.2% completed their learning results with an average score of 54.4. The test result data for cycle I showed that students who obtained a score of > 70 were 9 or 50% students with an average score of 66.4, while the test result data from cycle II showed that students who obtained a score of > 70 were 15 students or 83.3% with an average score of 76.1. The results of observation of student activities in the first cycle as many as 73.1% were in the good category, while in the second cycle reached 80.8% in the very good category.